The relation between maternal emotional support and child physiological regulation across the preschool years. Issue 4 (9th May 2012) - Perry, Nicole B.; Nelson, Jackie A.; Swingler, Margaret M.; Leerkes, Esther M.; Calkins, Susan D.; Marcovitch, Stuart; O'Brien, Marion
Abstract Trajectories of baseline RSA (respiratory sinus arrhythmia), an index of reactivity, and vagal withdrawal, an index of regulation, across the preschool period were examined. In addition, maternal emotional support was investigated as a potential time‐varying predictor of these trajectories. Physiological measures were obtained during frustration tasks, and a maternal emotional support measure was assessed via maternal report and direct observation. Children's baseline RSA and vagal withdrawal scores were moderately stable across the preschool period. Growth models indicated that children's baseline RSA scores changed linearly over the preschool years, and there was significant variability in withdrawal trajectories. Greater maternal emotional support predicted higher initial withdrawal levels and lower emotional support was associated with the greatest increase in withdrawal over time. This suggests that children of higher emotionally supportive mothers reached higher levels of physiological regulation earlier in development and therefore did not show the same increase across preschool as children of less supportive mothers. Maternal emotional support was not significantly related to trajectories of baseline RSA. © 2012 Wiley Periodicals, Inc. Dev Psychobiol 55: 382–394, 2013